Retrospective study on anemia prevalence of pregnant women during third trimester pregnancy in Yogyakarta 2019 - Fitnaningsih Endang Cahyawati; Retno Mawarti; Dyah Ayu Utari; Agus Gunadi (Universitas 'Aisyiyah Yogyakarta, 2021)
Anemia during pregnancy can result in fetal death, abortion, congenital defects, low birth weight, reduced iron reserves in children or children born with malnutrition. This study aimed to describes the anemic incidence in the third trimester of pregnant women at Puskesmas Tegalrejo Yogyakarta. This research was a descriptive study that used a retrospective time approach. A total of 212 pregnant women in the third trimester met the inclusion criteria, which was pregnant women in the third trimester who had their pregnancy checked at the Puskesmas Tegalrejo Yogyakarta. The research tool used was a data collection sheet. Data was analyzed in proportion and percentage then using Chi Square analysis to get the correlational value (p0.05). Odds Ratio for Cohort value toward anemic status also was analyzed. The incidence rate of anemia (Hb 11gr%) occurred in 44 (20.8%) mothers aged 20 years and 35 years, 58 (27.4%) mothers with gestational age 37 weeks, 137 (64.6%) mothers with 4 parity, with a pregnancy interval of 24 months from the last child, as many as 141 (66.5%) mothers and 110 (51.9%) mothers with nutritional status based on upper arm circumference 23.5cm. These factors are considered risk factors for causing anemia in pregnant women. Correlation test using Chi Square is known to show p 0.05 for all variables. The highest risk for Anemic Incidence was known to be indicated by the Pregnancy Interval factor, 24 months (p 0.001; OR 9,512) followed by parity 4 (p 0.001; OR 6,679).